Motivating Students With Dyslexia: The Debilitating Effects of Normative Performance Goals on Their Physiological Arousal - Alkhadim, Ghadah S. (Frontiers in Education, 2022)
The present study tested the hypothesis that normative versus non-normative performance goals would be associated with significantly divergent pathways in relation to both cognitive and emotional regulation. Participants were 16 college students with a diagnosis of dyslexia. Students were subjected to an experimental induction of normative and non-normative performance goals while engaged in reading pseudowords. Students’ EEG activation, EMG, and BVP were assessed during baseline, relaxation, and experimental conditions. Results indicated that the normative goal condition was associated with lower amplitudes in alpha and beta waves, suggesting the presence of a slow cortical disorder. Furthermore, EMG and HR variability were at higher levels during the normative goal condition, suggesting elevated levels of anxiety and stress. It is concluded that normative performance goals are associated with divergent regulatory mechanisms compared to non-normative performance goals, which are quite stressful for individuals with dyslexia.